2009
DOI: 10.1080/09585190802707433
|View full text |Cite
|
Sign up to set email alerts
|

Organisational culture and commitment: a study of an Indian software organisation

Abstract: Although it has been suggested that both organisational culture and organisational commitment are important topics of contemporary organisational significance, there has been little attempt to explore the dynamics of these two concepts by scholars. The study reported in this paper adopts a three perspective framework (Martin 1992(Martin , 2002 to explore the impact of organisational culture on organisational commitment in a context (software sector in India) that is renowned to be dynamic and people-centred. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…First, they empirically support the argument that for employees who have experienced a career change, positive perceptions of organizational culture lead to a high level of both recognition of HR functions and commitment to their organizations. The findings of this study support previous studies that have reported a positive influence of organizational culture on HR functions and organizational commitment (Mathew and Ogbonna ; Taylor et al. ; Toh, Morgeson and Campion ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, they empirically support the argument that for employees who have experienced a career change, positive perceptions of organizational culture lead to a high level of both recognition of HR functions and commitment to their organizations. The findings of this study support previous studies that have reported a positive influence of organizational culture on HR functions and organizational commitment (Mathew and Ogbonna ; Taylor et al. ; Toh, Morgeson and Campion ).…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between organizational culture and organizational commitment has been the focus of considerable scholarly research (Mathew and Ogbonna 2009;Mathieu and Zajac 1990;Silverthorne 2004). Organizational characteristics reflecting organizational culture (e.g.…”
Section: Relationships With Hr Functions and Organizational Commitmentmentioning
confidence: 99%
“…This has led employers to focus on the development of their human capital to deliver more with fewer investments [1]. Therefore, if employees commitment is their degree of identification with the missions and goals of the organisation and the willingness to remain in it, it follows therefore that the employers should embark on activities that will enable them retain the skilled, talented and committed workforce [25]. In literature, four general antecedents such as personal characteristics, job characteristics, Work experience and Role related characteristics have been identified [26].…”
Section: Organisational Commitmentmentioning
confidence: 99%
“…The peculiar nature of work in the software industry, with its emphasis on work teams that are formed and disbanded according to projects, would give rise to different patterns of socialization, thereby affecting culture and commitment in a variety of ways. In the software sector, sophisticated cultural and commitment practices are likely to be prevalent (Kwantes, ; Mathew & Ogbonna, ; Paul & Anantharaman, ). Summaries of other studies follow.…”
Section: Previous Octapace Researchmentioning
confidence: 99%